Mitigating the 'Green Premium' Barrier: How Digital Information Richness and Material Transparency Enhance Customer Trust in High-Priced Sustainable Products (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The global paradigm shift towards sustainable consumption is frequently hindered by the "Green Premium" the additional cost associated with eco-friendly products. While classical economic theory suggests that high prices deter purchase intention, this study posits that in the digital marketplace, the primary barrier is information asymmetry, not merely price. Integrating Signaling Theory and the Information Systems (IS) Success Model, this research investigates how the quality of information provided by e-commerce platforms moderates the negative relationship between price and customer trust. We analyzed a secondary dataset of 3,587 eco-friendly products from Amazon, employing text mining techniques to quantify "Information Granularity" (description depth) and "Material Transparency." The findings reveal a paradox: while higher prices generally diminish customer trust, this negative effect is significantly attenuated when the product page exhibits high information richness. This study contributes to the literature by demonstrating that Information Systems function as a critical validation mechanism that justifies the green premium, shifting consumer focus from cost to value.